The reality of using social networks as an educational medium from the point of view of the faculty members at Umm Al-Qura University - Maghribi, Ranih Sueud (Journal of Educational and Psychological Sciences, 2021)
The study aimed to uncover the reality of using social media as an educational medium from the point of view of faculty members at Umm Al-Qura University, and in order to achieve the objectives of the study, the researcher used the descriptive approach by applying a questionnaire consisting of (39) statements distributed in two areas, namely the degree of use of faculty members at Umm Al-Qura University Social media networks and the second field have the degree of importance of using social media as an educational medium from the point of view of the faculty members at Umm Al-Qura University, and it was distributed among a sample of the faculty members at Umm Al-Qura University of (118) members, and the study showed several results, the most important of which were: The faculty members at Umm Al-Qura University use social media networks as an educational medium to a large extent and with an average of (3.65), and that the use of social networks as an educational medium is very important, as the arithmetic average reached the importance of using social networks as an educational medium from the point of view of the faculty members at Umm Al-Qura University (4.35) And the existence of statistically significant differences in the importance of using social networks as an educational medium according to the variable years of service in favor of the category (less than 5 years).
Keywords: social media; Umm Al-Qura; faculty members; e-learning